"If you tolerate this ..." : the Spanish Civil War in the age of total war - Baumeister, Martin HerausgeberIn; Schüler-Springorum, Stefanie 1962- HerausgeberIn (Campus-Verl, 2008)
The Spanish Civil War has been called the "quintessential expression" of the violent confrontation of the great ideologies in the Europe of the 1930s. Yet, historical research has so far paid all but no attention to the Spanish experience within the context of the wars of the 20th Century. This "age of total war" has been dominated like no other by the mass mobilization, military violence, mass killing and mass dying. The previous differentiation between civilian and military sectors collapsed while war itself dominated all human activity and almost all areas of experience, burning itself deep into the individual’s memory and into collective identities. In this volume, reknown scholars from the US, Great Britain, Spain, Italy and Germany situate the Spanish Civil War in the context of total war by focussing on topics like military violence, war experience and the culture of war.